STRATEGI KOMUNIKASI POLITIK PUTERI KOMARUDIN MELALUI MEDIA SOSIAL INSTAGRAM - Alvia Ayu Pradya; Irawati Irawati; Susi Dian Rahayu (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2023)
In the current era of globalization, the high level of information technology has rapidly givenrise to new media (social media) in life. The existence of social media today greatly affectsvarious areas of life in society, including the political field. So that now many politicians arecompeting to campaign through various types of social media, especially Instagram socialmedia. Because the media today plays an increasingly large role in the political life anddemocracy of a nation. Puteri Anneta Komarudin is a political leader who actively uses socialmedia Instagram to interact and convey aspirations to the community. This study aims todetermine the communication strategy used by Puteri Komarudin through Instagram socialmedia in increasing the role of legislation and the political image of the DPR-RI in thecommunity. This research uses descriptive qualitative methods with documentary datacollection techniques. The result of this research is that Puteri Komarudin has communicatedthrough social media with 4 message strategies that have succeeded in making PuteriKomarudin closer and known to the community and increasing public trust in people'srepresentatives.